(untitled) (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2018)
Objectives: To measure the Tweed’s norms for Bangladeshi population. Method: Total of 100 samples was collected from students and doctors of Dhaka Dental College and other hospitals aged between 18-26 years of age. Among the samples 52 were male and 48 were female. Mean age of male samples were 22.06 whereas mean age of female samples were 21.81 combined mean age of 100 samples were 21.94. Period of study was From July’2013 to Dec’2013. Results: The values of FMA, FMIA and IMPA for Bangladeshi male subjects were found 23.02, 54.5 and 102.27. For the female samples the values were 21.5, 53.92 and 104.69 respectively. The values of FMA, FMIA and IMPA for Bangladeshi population were found as 22.29, 54.22 and 103.43. Whereas for Caucasians the parameters were 24.6, 68.2, 86.9. Conclusion: The value of FMA, FMIA, IMPA for Bangladeshi population were measured. The difference of values of FMA, FMIA, IMPA of Bangladeshis with Caucasians were found statistically significant. Whereas the difference of values of FMA, FMIA, IMPA of Bangladeshis with North Indians were found statistically insignificant. Ban J Orthod & Dentofac Orthop, April 2015; Vol-5 (1-2), P.8-12